Role of Homoeopathy in Management of Post Traumatic Stress Disorder (PTSD) Post COVID 19 (Advancements in Homeopathic Research, 2022)
Novel Corona virus/ COVID 19 infection is a severe pandemic that has involved the whole world. It not only causes severe physical morbidity but also has a negative impact on mental state of the individual. It has created an environment of stress and anxiety in all health workers and persons who are in close contact of infected individuals due to continuous work without rest and separation from family for work or quarantine purpose. Moreover there is also fear and stress in COVID- 19 patients due to uncertainty of treatment.Also general public also succumbing to mental agony due to lockdown and social impact of this pandemic. All these conditions may lead to Post traumatic stress disorder (PTSD). As mental well-being of a person is very important for productive life of a nation, so it is important that we also focus our attention towards long term effect of this outbreak like post COVID- 19 PTSD. Homoeopathy can offer a better alternative for various psychiatric disorders including PTSD. This is an attempt to understand the scope of homeopathy in the management with a therapeutic guide of PTSD post COVID 19.
Keywords: Post Traumatic Stress Disorder; PTSD; COVID 19; Homoeopathy